Psychometric Evaluation of the Chinese Version of the Decision Regret Scale - Xu, Richard Huan; Zhou, Ling Ming; Wong, Eliza Laiyi; Wang, Dong; Chang, Jing Hui (Frontiers in Psychology, 2020)
Objective The objective of this study was to evaluate the psychometric properties of the Chinese version of the decision regret scale (DRSc). Methods The data of 704 patients who completed the DRSc were used for the analyses. We evaluated the construct, convergent/discriminant, and known-group validity, internal consistency and test-retest reliability, and the item invariance of the DRSc. A receiver operating characteristic curve was employed to confirm the optimal cutoff point of the scale. Results A confirmatory factor analysis indicated that a one-factor model fit the data. The internal consistency (α=0.74) and test-retest reliability (intraclass correlation coefficient=0.71) of the DRSc were acceptable. The DRSc demonstrated unidimensionality and invariance for use across the sexes. It was confirmed that an optimal cutoff point of 25 could discriminate between patients with high and low decisional regret during clinical practice. Conclusion The DRSc is a parsimonious instrument that can be used to measure the uncertainty inherent in medical decisions. It can be employed to provide knowledge, offer support, and elicit patient preferences in an attempt to promote shared decision-making.